Pengelolaan Polder Banger Berbasis Kebersamaan antar Stakeholder - Zulfan, James; Hana, Maria Asunta (Jurnal Sosial Ekonomi Pekerjaan Umum, 2013)
Semarang is one of the cities in Indonesia that is frequently flooded especially in rainy season. The flood becomes inevitable due to the city’s proximity to the sea, high rainfall intensity, plus the land subsidence in some areas. To overcome this problem, an integrated system is needed. One of the solutions from the government is to build a polder in Banger area. Polder is expected to be a solution to urban flooding that has been happening. During its development, there are several issues related to funding and management which are caused by lack of coordination and partnership among stakeholders. This study is conducted by interviewing related informants, field survey and discussion forum. The purpose of this study is to analyze the problems and arrange management strategies for polder Banger. Therefore the stakeholders, who are the government, private sector, and the community can work together in synergy.